Integrity monitoring using multi-GNSS pseudorange observations in the urban environment combining ARAIM and 3D city models - El-Mowafy, Ahmed; Xu, B.; Hsu, L.T. (TAYLOR & FRANCIS LTD, 2020)
© 2020 Mapping Science Institute, Australia and Surveying and Spatial Science Institute.